1998
DOI: 10.1002/(sici)1099-1344(199807)41:7<585::aid-jlcr115>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

11C-radiolabeling of hallucinogenic psilocin, a potential radioligand for studying the role of serotonin receptors in psychotic symptom formation

Abstract: The desmethyl compound, 4‐hydroxy‐N‐methyltryptamine (4), was synthesized via a four‐step reaction sequence starting from 4‐benzyloxyindole (1). Psilocin (4‐hydroxy‐N,N‐dimethyltryptamine), an indole hallucinogen, was labeled by N‐monomethylation of the side chain using the classical methylating agent [11C]CH3I in 20±5% (decay corrected from [11C]CH3I) radiochemical yield. Specific activities obtained ranged from 900‐2300Ci/mmol at EOS (end of synthesis). The radiosynthesis, semi‐preparative HPLC and formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The compounds were originally synthesized by chemists at the Sandoz laboratories in Switzerland (Hofmann et al, 1958;Troxler et al, 1959). Several investigators have subsequently reported on the chemical synthesis of psilocybin (Ono et al, 1973;Repke et al, 1981;Ametamey et al, 1998;Yamada et al, 1998;Nichols and Frescas, 1999;Sakagami and Ogasawara, 1999;Yamada, 2000;, but only a few on the synthesis of psilocin (Nichols and Frescas, 1999;.…”
Section: Chemical Synthesis Of Psilocybin and Psilocinmentioning
confidence: 99%
“…The compounds were originally synthesized by chemists at the Sandoz laboratories in Switzerland (Hofmann et al, 1958;Troxler et al, 1959). Several investigators have subsequently reported on the chemical synthesis of psilocybin (Ono et al, 1973;Repke et al, 1981;Ametamey et al, 1998;Yamada et al, 1998;Nichols and Frescas, 1999;Sakagami and Ogasawara, 1999;Yamada, 2000;, but only a few on the synthesis of psilocin (Nichols and Frescas, 1999;.…”
Section: Chemical Synthesis Of Psilocybin and Psilocinmentioning
confidence: 99%
“…In addition, several recent studies have re-investigated the tolerability and efficacy of psilocybin in the treatment of anxiety-related advanced-stage cancer (Grob et al, 2009) and obsessive-compulsive disorders (Moreno et al, 2006). Other studies have focused on the pharmacokinetics (Hasler et al, 1997), metabolism (Hasler et al, 2002), dose-response effects (Hasler et al, 2004), and receptor mechanism of psilocybin (Ametamey et al, 1998;Hasler et al, 2009;Vollenweider et al, 1998Vollenweider et al, , 1999Vollenweider et al, , 2008. For example, we have shown that the selective 5-HT2A receptor antagonist ketanserin blocks the hallucinogenic effects of psilocybin in human subjects (Vollenweider et al, 1998), providing strong evidence for the link between 5-HT2A receptor activation and hallucinosis (Sanders-Bush et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to isolate 1 and 2 from the mushroom on a gram scale for use as pure standard compounds because 1 easily decomposes and 2 has a high polarity. Several reports on the synthesis of 1 have been published, while reports on the synthesis of 2 are few. ,, We report herein concise large-scale syntheses of psilocin ( 1 ) and psilocybin ( 2 ) that were achieved without any chromatographic purification.…”
mentioning
confidence: 99%